Prevalence of Menopause Symptoms among Iranian Women - Mojgan Asadi; Zahra Jouyandeh; Farnaz Nayebzadeh (Tehran University of Medical Sciences, 2012)
Objective: The aim of this study was to determine the symptoms associated with menopause among women referred to menopause clinic of Tehran Women General Hospital. Materials and methods: In this cross sectional study which has been done between January 2011 and January 2012, in  menopause clinic of Tehran Women's General Hospital 134 women were studied. For each woman a questionnaire was completed. The data gained from each questionnaire were  analyzed using SPSS version 13. Results: The mean age of natural menopause onset was 47.35 (SE=0.11) year. The symptoms associated with menopause were hot flushes (59.5%), mood swing (42.6%), vaginal dryness (41.1%) sleep problems (40.4%), night sweats (38.2%), memory loss (32.3%), urinary symptoms (18.3%), palpitation (6.6%), anxiety (5.8%), Joint and muscle pain (59.9%), depression (4.4%), Irritability (3.6%).. Conclusion: This study showed that hot flushes, mood swing and vaginal dryness were the most common symptoms associated with menopause.